2002
DOI: 10.1021/jp0266345
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Gas-Phase Amino Acid Alanine by Synchrotron Radiation Photoelectron Spectroscopy

Abstract: Valence and C1s core level photoelectron spectra of gaseous alanine have been recorded with synchrotron radiation. Using ab initio Green's Function calculations of the vertical outer valence ionization energies and CMS-XR calculations of the orbital ionization cross-sections, it is possible to account well for the features of both the new hν ) 92 eV valence photoelectron spectrum and also its differences with an earlier hν ) 21.2 eV spectrum. Good agreement may be achieved by considering just the contribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
99
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(115 citation statements)
references
References 40 publications
15
99
1
Order By: Relevance
“…Godfrey et al [64] emphasized that a rapid conversion from CF2 to CF1 was very probable due to large vibrational amplitudes of the low frequency modes. But more recently, Powis et al [27] showed that, both experimentally and theoretically, Ala could be observed in the two low-lying conformations. Moreover, the zero point energy and the thermal corrections on the energetic and entropic terms can also be responsible for an increased or a decreased separation between the conformers as can be seen from the results in Table 6.…”
Section: Thermodynamical Relative Stabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Godfrey et al [64] emphasized that a rapid conversion from CF2 to CF1 was very probable due to large vibrational amplitudes of the low frequency modes. But more recently, Powis et al [27] showed that, both experimentally and theoretically, Ala could be observed in the two low-lying conformations. Moreover, the zero point energy and the thermal corrections on the energetic and entropic terms can also be responsible for an increased or a decreased separation between the conformers as can be seen from the results in Table 6.…”
Section: Thermodynamical Relative Stabilitymentioning
confidence: 99%
“…Several conformations were already optimized and studied in the literature [27,48,[57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76] and are referenced in the Table. The species labeled S-Thr corresponds to a threonine where the chirality of the C β (which is R in the natural Thr) is reversed. By comparing Thr and S-Thr, it turns out that the CF1 conformations present the same hydrogen-bonding patterns while the CF2 ones are permuted: the H-bonding pattern of CF2 (1) in Thr corresponds to that of CF2 (2) in S-Thr and vice-versa.…”
Section: Relative Stability Of the Neutral Conformersmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the G3MP2 global minima for neutral amino acids match structures inferred from microwave and other gas-phase spectrometric methods. The examples include glycine [3,5], alanine [11][12][13][14][15], isoleucine [16], leucine [17], serine [15,18], tryptophan [19], and valine [20,21]. However, there are some examples in the literature of global minima identified with the B3LYP functional that do not match experimental structures (although many do match).…”
Section: Assessment Of Theoretical Approachmentioning
confidence: 99%
“…Powis et al [4] reported on the valence and C 1s core level photoelectron spectra and quantum calculations of gaseous alanine and threonine. Jochims et al [5] reported an extensive photoionization study in the 6-22 eV energy range, using quadrupole mass spectrometry, of fi ve amino acids: glycine, α-alanine, β-alanine, α-aminoisobutyric acid and α-valine.…”
Section: Introductionmentioning
confidence: 99%